Self-management Strategies for Risk Reduction of Subclinical and Mild Stage of Breast Cancer–Related Lymphedema: A Longitudinal, Quasi-experimental Study. Issue 6 (November 2021) - Liu, Fei; Li, Fenglian; Fu, Mei R.; Zhao, Quanping; Wang, Yingxin; Pang, Dong; Yang, Ping; Jin, Sanli; Lu, Qian
Abstract : Background: Early intervention with self-management strategies can potentially reduce the risk of progression of breast cancer–related lymphedema (BCRL). Objective: To determine if The-Optimal-Lymph-Flow (TOLF) program focused on self-management strategies applied to patients with a subclinical or mild stage of BCRL can improve lymphedema-related behaviors, symptom experience, and limb circumference changes. Methods: A total of 41 women with subclinical or mild lymphedema were enrolled in TOLF program. Lymphedema-related behaviors and lymphedema-related symptom experiences were measured by the Breast Cancer and Lymphedema Symptom Experience Index, and limb circumference changes were measured by sequential circumferential limb measurements at baseline and 1, 3, 6, and 12 months after the intervention. Generalized estimating equations were used to estimate the effects of the intervention on outcomes. Results: Generalized estimating equations revealed that lymphedema-related behaviors and the number and severity of lymphedema-related symptoms were significantly improved at 4 postintervention test points compared with baseline (all P < .001). Reduced lymphedema-related symptom distress in functional, social, emotional, and psychological and self-perception (all P < .01) also resulted. The majority (77.5%) of patients maintained their preintervention lymphedema status; 17.5% of them reversed from mild lymphedema to subclinical lymphedema; 5.0% of them had lymphedema status progression. Conclusion: Positive outcomes in terms of lymphedema-related behaviors, relieving lymphedema-related symptom experience, and halting the progression of lymphedema status were documented following TOLF. Implications for Practice: Nurses could educate patients to incorporate the self-management strategies of TOLF program into daily life to help patients prevent or reverse subclinical or mild stage of BCRL.